Measurement, modelling and evaluation of dependable computer and communication systems : 18th International GI/ITG Conference, MMB & DFT 2016, Münster, Germany, April 4-6, 2016, proceedings /: 18th International GI/ITG Conference, MMB & DFT 2016, Münster, Germany, April 4-6, 2016, proceedings. (2016) - Unknown
No abstract available